2014
DOI: 10.1111/pcmr.12253
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of common polymorphisms within the human Tyrosinase locus and genetic association with pigmentation traits

Abstract: Summary We have compared the melanogenic activities of cultured melanocytes carrying two common TYR alleles as homozygous 192S-402R wildtype, heterozygous and homozygous variant. This includes assays of TYR protein, DOPAoxidase activity, glycosylation and temperature sensitivity of protein and DOPAoxidase levels. Homozygous wildtype strains on average had higher levels of TYR protein and enzyme activity than other genotypes. Homozygous 402Q/Q melanocytes produced significantly less TYR protein, displayed alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(74 citation statements)
references
References 60 publications
3
70
0
1
Order By: Relevance
“…The 192Y allele is associated with light skin, eye colour, absence of freckles and an increased SCC risk, whereas the 402Q change was reported to increase the risk of BCC [43] , was frequently associated with albinism patients [44] and significantly increased SK, multiple melanoma risk [42] and familial CM risk in a French population [41] . Protein expression studies have shown that the 402Q variant encodes a thermolabile enzyme [40] , and in primary melanocyte cultures we have shown that it is retained in the endoplasmic reticulum, hypoglycosylated and preferentially degraded [45] . Interestingly, thermolabile TYR alleles are the basis of the Siamese/Burmese cat coat colours, where pigment appears darkest at the extremities of the body [46] ; this condition is also present in some human albino patients as subtype OCA1B [39] .…”
Section: Tyr (Oca1)mentioning
confidence: 99%
See 2 more Smart Citations
“…The 192Y allele is associated with light skin, eye colour, absence of freckles and an increased SCC risk, whereas the 402Q change was reported to increase the risk of BCC [43] , was frequently associated with albinism patients [44] and significantly increased SK, multiple melanoma risk [42] and familial CM risk in a French population [41] . Protein expression studies have shown that the 402Q variant encodes a thermolabile enzyme [40] , and in primary melanocyte cultures we have shown that it is retained in the endoplasmic reticulum, hypoglycosylated and preferentially degraded [45] . Interestingly, thermolabile TYR alleles are the basis of the Siamese/Burmese cat coat colours, where pigment appears darkest at the extremities of the body [46] ; this condition is also present in some human albino patients as subtype OCA1B [39] .…”
Section: Tyr (Oca1)mentioning
confidence: 99%
“…Interestingly, thermolabile TYR alleles are the basis of the Siamese/Burmese cat coat colours, where pigment appears darkest at the extremities of the body [46] ; this condition is also present in some human albino patients as subtype OCA1B [39] . Recent studies have shown that the TYR genotype is likely to be a significant modifier of other pigmentation gene polymorphisms in human skin, hair and eye colour, and associated with naevus count, though not apparent by body site there is potential for thermal changes in pigmentation of the skin and hair [45] . The 2 polymorphisms were present on 4 TYR haplotypes, designated as WT being 192S-402R, single variants 192Y-402R and 192S-402Q, with a double-variant 192Y-402Q of low frequency at 1.9%.…”
Section: Tyr (Oca1)mentioning
confidence: 99%
See 1 more Smart Citation
“…However, functional studies reported that 192Tyr and 402Gln alleles have reduced TYR enzyme activity. Heterozygous p.Ser192Tyr and p.Arg402Gln variants caused significant reduction in TYR expression, and a consistent decrease in TYR protein levels was observed in homozygous p.Ser192-Tyr cells [9].…”
Section: Discussionmentioning
confidence: 70%
“…Differing degrees of skin pigmentation observed among ethnic groups can also be partially attributed to differences in tyrosinase activity, some of which is accounted for by genetic variants at the TYR (Jagirdar et al, 2014) and IRF4 loci (Praetorius et al, 2013). Tyrosinase, the rate-limiting enzyme required for melanin synthesis, is quantitatively more active in melanocytes from darker skin than lighter skin (Pomerantz and Ances, 1975; Iozumi et al, 1993; Iwata et al, 1990; Maeda et al, 1997), despite similar RNA expression levels (Naeyaert et al, 1991).…”
Section: Introductionmentioning
confidence: 99%